Book loan delinquency in the University of the Philippines Libraries (Diliman) its causes and extent - Matulac, Luzviminda J.; Cruz, Ma. Divina P.; Arlante, Salvacion M. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1996)
The main objective of this study is to determine the causes and extent of book loan delinquency in the University of the Philippines (Diliman) libraries, school year 1994-1995. Specifically, the study sought to answer the following questions: 1) what are the factors/causes contributing to book loan delinquency among UP Diliman libraries' clients? 2) what are the subject fields of books mostly affected by book loan delinquency? 3) how many percent of the total number of books borrowed are unreturned for the second semester, 1994-1995n 4) how many percent of the total number of registered borrowers are delinquent users for second semester, 1994-1995n 5) what are the existing control measures to minimize book loan delinquency? 6) what are other measures or procedures to minimize if not to prevent book loan delinquency?
The study utilized the descriptive and correlational methods. It was conducted among 333 students, faculty and staff respondents and 21 head librarians of the college libraries. Two sets of questionnaires were used as main instrument of the study. The first set was intended for the student, faculty, staff respondents and the second for the head librarians. An interview was also conducted to follow-up answers to the main instrument. The Slovin's formula was employed to determine the number of respondents from each college to be included in the study. Frequency distribution and percentages were used for the descriptive analysis of the data. The SPSS PC+ (Statistical Package for the Social Science) software was used to determine the extent of relationship between variables.
Majority of the respondents are less than 20 years old, are females, are juniors in the undergraduate program and are enrolled in 15 to 20 credit units. The faculty and staff respondents are also females, on the 31 above age bracket, with a teaching load of less than 20 units. The staff, on the other hand are enrolled in the graduate studies.
The type of books kept overdue by the respondents are circulation or home reading books. Majority of the subject areas affected by book loan delinquency are Social Sciences, followed by Science and Technology, and Humanities. With regard to the extent of book loan delinquency, the percentage of total number of unreturned books is: students (.7 percent); faculty (6.4 percent); staff (9.4 percent). Only five percent of the total number of registered student borrowers are delinquent users.
This study was able to test the relationships between economic and personal factors; library and academic factors with book loan delinquency. The economic factors which tend to influence book loan delinquency of student, faculty and staff are: income, availability of study materials and the photocopying of reading materials.
The library factors that possibly cause book loan delinquency are: frequency of use of the library and borrowing of books, type of books borrowed, loan period, and limited copies of books. The respondents also consider the academic factors which affect book loan delinquency; bulk of assignments/classroom requirements like: readings, research papers/theses, written reports, term papers, preparing papers on lectures, seminars, conferences, speeches, etc. Other than the above factors that contribute to book loan delinquency the following were cited: borrowers have classes at the time of returning the book, lack of time due to work, and someone borrowed the book.
The suggestions and recommendations cited by the respondents are recommended in the study. Library authorities 1) should review the policies, rules and regulations particularly on borrowing of books, like: the number of books one can borrow, the loan period, renewal of books, etc.; 2) should be consistent and strict in implementing the policies and guidelines they had formulated on book loan; 3) should determine the need for a certain book and purchase the necessary number of copies needed; 4) should provide a convenient way to check out, return or renew books in the library. There should be rotation of personnel manning the borrowing and return desks during noon break; 5) should clearly present to the students at the start of the year through library orientation as well as to newly hire faculty and staff of the University library rules and regulations on borrowing of books and the importance of sharing library resources; and 6) should undertake a replication of the study and cost analysis of the subject in other UP campuses.
Typescript.
Vita.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Libraries -- Circulation loans